Michel Foucault and Counter-History - Márquez Estrada, José Wilson (Universidad Pedagógica y Tecnológica de Colombia, 2014)
This article analyzes the historiographical proposal of Michel Foucault and the characteristics of his genealogical method. Furthermore, the problem of the subject and the concept of event embedded in the context of his historic proposal will be examined. This study encompasses the analysis of important aspects, such as the question of method articulated with the speciic role of the Historian, proposed by Foucault as a genealogical and archeological exercise. In this regard, a differential analysis of both of these concepts and their role in Foucault’s historiographicalproposal will be analyzed, as well as the problem of the subject and its importance in the context of Foucault’s work. In the inal section, the value of the Foucauldianhistoriographical vision in the context of the Western historiography will be presented. Emphasis will be placed on its break-up with the traditional history, understood ascounter-history.